Development of biomimicry application framework for sustainable design - Othmani, Nurul Izzati (2022)
Biomimicry is a design in the field of science which studies nature as a model and draws inspiration from it. In this light, nature’s design and processes are mimicked to solve problems facing humans and the world around them. This field presents enormous capabilities and potential for exciting future technologies. However, out of the three levels of biomimicry, only the organism level biomimicry has been widely applied as a tool to achieve a design solution. Thus, understanding biomimicry application and levels of mimicking are also crucial in promoting it. Developing a framework that connects the three levels of biomimicry is necessary to produce a sustainable design. Hence, this research proposes a framework that can guide the application of biomimicry to achieve sustainable design. This study adopted the KJ method, where the qualitative method is supported by a quantitative component, to identify the design elements has been inspired by or applied in biomimicry. The study also distributed a survey questionnaire involving 134 respondents. This method was employed to gauge the participant’s understanding and knowledge of biomimicry. The third method involved focus group discussions in conducting an expert validation of the proposed framework. The findings showed that the knowledge and understanding of biomimicry at the educational level are important in applying biomimicry in designs. Therefore, it is crucial to have a framework that guides designers in promoting and implementing biomimicry for a sustainable environment. Other than that, as more designs are inspired by nature, it may help facilitate the sustainable growth of towns and cities, sustain and enhance people’s well-being, and improve their quality of life.